Effect of Domestic Debt on Selected Macroeconomic Variables in Nigeria: An Empirical Analysis - Nduka, Joseph Afamefuna; Achugbu, Austin (African Journal of Education,Science and Technology (AJEST), 2014)
The study is an empirical investigation into the effect of domestic debt on selected macroeconomic variables in Nigeria. The explanatory variables include GDP (Gross Domestic Product) for the overall performance of the economy, financial deepening (FIN) to capture the effect on the financial sector while foreign exchange rate (FEX) captures the effect on external sector. The study used time series data for a period of 27 years spanning 1986 to 2012. The period of the study was chosen to start in 1986 when Nigeria economy assumed market based status. The Ordinary Least Square regression technique was used for the analysis. The results showed that about 82% of changes in domestic debt stock can be explained by fluctuations in the explanatory variables. Further analysis from the result showed that domestic debt has no significant effect on GDP growth and exchange rate in Nigeria. Moreover, domestic debt has significantly and positively influenced financial deepening. Hence, the study concludes that domestic debt has helped to beef up the amount of money in circulation thereby making available investible funds into the productive sectors. However, to ameliorate the negative effect of domestic debt on the economy, it is expected that the apex legislative body should restrain imprudent borrowing by the executive and ensure loan borrowed must be project-tied and must get nation-wide consultation before embarking on such loan.